2007
DOI: 10.1109/tim.2007.899904
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fiber-Optic Tapered Long-Period Grating Sensor for Pressure Monitoring

Abstract: Abstract-The method and the required installations for fabricating tapered long-period fiber gratings can be simpler than that of standard fiber Bragg gratings, and the fabrication process is faster. To our knowledge, the tapered long-period fiber grating pressure sensor is presented here for the first time. In this paper, the fabrication method for tapered long-period fiber gratings, the sensing principle, the sensor structure, the measurement setup, and the preliminary results are presented and discussed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 6 publications
0
72
1
Order By: Relevance
“…Bock et al [70] reported a tapered long period Bragg grating pressure sensor with a pressure sensitivity of 51 pm/MPa, which was significantly greater than a bare standard FBG. LPGs have the potential to have custom designed sensitivities, however, the manufacturing process is usually expensive and time consuming.…”
Section: Fbg Pressure Sensorsmentioning
confidence: 99%
“…Bock et al [70] reported a tapered long period Bragg grating pressure sensor with a pressure sensitivity of 51 pm/MPa, which was significantly greater than a bare standard FBG. LPGs have the potential to have custom designed sensitivities, however, the manufacturing process is usually expensive and time consuming.…”
Section: Fbg Pressure Sensorsmentioning
confidence: 99%
“…The fiber consists of Gedoped fused silica core, fused silica cladding and exterior polymer coating that could be mechanically removed. Gratings were manufactured using a computer-assisted arc discharge system [6,7]. The method is based on periodic melting and re-solidifying of areas of the fiber in order to create refractive index variation and slight periodic tapering.…”
Section: Lpg Fabricationmentioning
confidence: 99%
“…They report a sensitivity of 31.67 nm/ MPa and 3.55 nm/MPa, respectively. Pressure sensors using long period gratings [15] and microstructured optical fibers [16] have also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%